'A women's war against war: The socialist-feminist pacifism of Four Lights: An Adventure in Internationalism'. (30th November 2018) - Schreiber, Rachel
Abstract : The New York City Women's Peace Party (NYC-WPP) published the first issue of Four Lights: An Adventure in Internationalism on 27 January 1917. The inaugural issue opened with the founders' mission to 'voice the young, uncompromising woman's peace movement in America' and declared the publication's anti-war and anti-militarist position to be 'daring and immediate'. In the short span of the nine months between January and October that Four Lights issued fortnightly numbers, its editors staked and held onto the staunch anti-war stance and Four Lights braided pacifism together with feminism. Their entwined anti-capitalist perspectives on gender, labour, class and race can be understood as anticipating intersectional feminism. Not nearly as well known as The Woman Citizen, The Suffragist and other publications of the women's national suffrage and Progressive presses, Four Lights offers a fascinating glimpse into the thinking of the most ardent pacifists of the 1910s. This study of Four Lights illuminates this history and situates the journal's critical place in the history of radical American periodicals.